Two truths and a lie - Henry, April (Christy Ottaviano Books/Little, Brown and Company, 2022)
"When a troupe of theater students get stranded in a creepy old motel during a blizzard, they play a foreboding game of truth and lies that leads to real danger when a murderer is discovered in their midst"--